12x-3(3x-6)=18+3x

Simple and best practice solution for 12x-3(3x-6)=18+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3(3x-6)=18+3x equation:


Simplifying
12x + -3(3x + -6) = 18 + 3x

Reorder the terms:
12x + -3(-6 + 3x) = 18 + 3x
12x + (-6 * -3 + 3x * -3) = 18 + 3x
12x + (18 + -9x) = 18 + 3x

Reorder the terms:
18 + 12x + -9x = 18 + 3x

Combine like terms: 12x + -9x = 3x
18 + 3x = 18 + 3x

Add '-18' to each side of the equation.
18 + -18 + 3x = 18 + -18 + 3x

Combine like terms: 18 + -18 = 0
0 + 3x = 18 + -18 + 3x
3x = 18 + -18 + 3x

Combine like terms: 18 + -18 = 0
3x = 0 + 3x
3x = 3x

Add '-3x' to each side of the equation.
3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x-x(.25)=42000 | | 11(w+2)+14=2 | | 15b-2b=-9 | | 6x-30=7-2x | | 2x+3+6x-1=8x+2 | | -2(4+m)=10 | | 2x+3+6X-1=x+2 | | 27j-6=14j-7 | | 112=7w-168 | | 30m=22+80m | | 2x+24=-30+5x | | 21x+7=10x-1 | | 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= | | 15=k-32 | | 3x+2-2=8-2 | | 18p-15=0 | | T(-3)=21 | | 2X+1=-x+2 | | -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 | | (x^2)+30x-2000=0 | | n-11=66 | | 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 |

Equations solver categories